Onychiuridae of China: species versus generic diversity along a latitudinal gradient - Xin Sun; Louis Deharveng; Anne Bedos; Donghui Wu; Jian-xiu Chen (Soil Organisms, 2024)
Our knowledge of Chinese Onychiuridae (sensu Deharveng 2004) accelerated during the five last years. From 2008, we have recorded 29 species and six genera of Onychiuridae new for China, reflecting an increase of 64 % in the number of species and 46 % in the number of genera for the country. Twenty-one of these species were new to science. Today, there are 45 described species belonging to 13 genera of Onychiuridae in China. Their diversity pattern exhibits a remarkable gradient in genus versus species diversity from southwestern China (14 species in four genera) to northeastern China (18 species in 10 genera). A checklist and a key to genera of Chinese Onychiuridae are given. Because huge regions of China remain unsampled or undersampled, and because species have narrow distribution, an increase in species number is likely to continue at the same pace in the coming years.